Evaluation of antibacterial efficacy of different exracts of ocimum gratissimum l. (lamiaceae) leaves against some pathogenic bacteria with phytochemical screening. - TANMAY GHOSH,; MOHAN KUMAR BISWAS,; RISHIN BHATTACHARYYA, (International Journal of Pharma and Bio Sciences, 2019)
The study aims to investigate the efficiency of Ocimum gratissimum against pathogenic bacteria which includes Escherichia coli, Salmonella entericaser Typhi and Staphylococcus haemolytic us using standard microbiological procedures. Ocimum gratissimum was harvested and air dried for 6-7 days. The stuff was processed into fine powdery. Benzene, Hexane, Chloroform, Ethyl acetate served as extraction solvent, and once extraction, the obtained plant extract was weighed and preserved underneath anti-microbial condition.. The extracts were poured into the wells at different concentrations of 50mg/ml, 100mg/ml, 200mg/ml and 400mg/ml. After incubation zones of inhibition were carried out by agar cup method was observed. Among five extracts, the zone of inhibition Screened best in ethyl acetate extract. In case of Salmonella entericaser Typhi: (MTCC 8767) the ethyl acetate extract (400 mg/ml) showed maximum zone of inhibition 17.3 ± 0.2 mm while benzene extract (50 mg/ml) showed minimum zone of inhibition 10.8 ± 0.1 mm In case of Staphylococcus haemolytic us: (MTCC 3383) the ethyl acetate extract (400 mg/ml) showed maximum zone of inhibition 18.0 ± 0.1 mm, while benzene extract (50 mg/ml) showed minimum zone of inhibition 11.6 ± 0.2 mm In the case of Escherichia coli:(MTCC 2872) the ethyl acetate extract (400 mg/ml ) showed maximum zone of inhibition 18.7 ± 0.2 mm, while benzene extract (50 mg/ml) showed minimum zone of inhibition11 ± 0.2mm. Hence Ocimum gratissimum can be employed in developing therapeutic drugs against many bacterium. Many studies have been reported for the presence of alkaloids, tannins, glucosides, B vitamins, water soluble vitamins etc., in Ocimum gratissimum leaves.